The early exercise boundary under the jump to default extended CEV model - Nunes, J. P. V.; Dias, J. C.; Ruas, J. P. (Applied Mathematics and Optimization, 2020)
This paper proves the existence, uniqueness, monotonicity and continuity of the early exercise boundary attached to American-style standard options under the jump to default extended constant elasticity of variance model of Carr and Linetsky (Financ Stoch 10(3):303–330, 2006).